The Immunomodulatory Effects of Active Ingredients From Nigella sativa in RAW264.7 Cells Through NF-κB/MAPK Signaling Pathways - Wei, Jinfeng; Wang, Baoguang; Chen, Yixiao; Wang, Qiuyi; Ahmed, Adel F.; Zhang, Yan; Kang, Wenyi (Frontiers in Nutrition, 2022)
Nigella sativa is a valuable herb for its functional compositions in both food and medication. N. sativa seeds can enhance immunity, anti-inflammation and analgesia and hypoglycemia, but most of the related researches are related to volatile oil and extracts, and the activity and mechanism of compounds is not clear. In this study, Ethyl-α-D-galactopyranoside (EG), Methyl-α-D-glucoside (MG), 3-O-[β-D-xylopyranose-(1 → 3)-α-L-rhamnose-(1 → 2)-α-L-arabinose]-28-O-[α-L-rhamnose-(1 → 4)-β-D-glucopyranose-L-(1 → 6)-β-D-glucopyranose]-hederagenin (HXRARG) and 3-O-[β-D-xylopyranose-(1 → 3)-α-L-rhamnose-(1 → 2)-α-L-arabinose]-hederagenin (HXRA) were isolated and identified from N. sativa seeds. In addition, four compounds could activate NF-κB pathway by promoting the expression of phosphorylation of P65 and IκBα, promoting the phosphorylation of JNK, Erk and P38 to activate MAPK signaling pathway, enhancing the proliferation and phagocytic activity of RAW264.7 cells, and promoting the release of NO, TNF-α and IL-6 on RAW264.7 cell in vitro. The results showed that N. sativa can be used as dietary supplement to enhance immune.